Registration of 'Colter' Wheat. Issue 3 (18th July 2014) - Berg, J. E.; Wichman, D. M.; Kephart, K. D.; Eckhoff, J. L.; Stougaard, R. N.; Lamb, P. F.; Miller, J. H.; Nash, D. L.; Grey, W. E.; Johnston, M.; Gettel, D.; Larson, R.; et al.
Abstract : 'Colter' (Reg. No. CV‐1099, PI 670156) hard red winter wheat ( Triticum aestivum L.) was developed and released by the Montana Agricultural Experiment Stations in September 2013. Colter was derived from the cross MT9982*2/BZ9W96‐895. MT9982 is a sib selection of 'Yellowstone', and BZ9W96‐895 is an unreleased breeding line of unknown pedigree developed by Westbred. Colter was developed using a modified bulk breeding method and selected as an F5:6 headrow. Colter was tested under the experimental number MT08172 in Montana yield trials from 2009 to 2013. Like Yellowstone, Colter is a high‐yielding, winter‐hardy hard red winter wheat line with medium to late maturity, medium to high grain protein, and acceptable milling and baking quality. Colter was released for its excellent performance in winter wheat production environments of north‐central Montana and its improved grain volume weight and stem rust (caused by Puccinia graminis Pers.:Pers. f. sp. tritici Eriks. & E. Henn.) resistance relative to Yellowstone.